Dissociation of Rad51 Presynaptic Complexes and Heteroduplex DNA Joints by Tandem Assemblies of Srs2 - Kaniecki, Kyle (2017)
Srs2 is a superfamily 1 (SF1) helicase and antirecombinase that is required for genome integrity. However, the mechanisms that regulate Srs2 remain poorly understood. Here, we visualize Srs2 as it acts upon single-stranded DNA (ssDNA) bound by the Rad51 recombinase. We demonstrate that Srs2 is a processive translocase capable of stripping thousands of Rad51 molecules from ssDNA at a rate of ∼50 monomers/s. We show that Srs2 is recruited to RPA clusters embedded between Rad51 filaments and that multimeric arrays of Srs2 assemble during translocation on ssDNA through a mechanism involving iterative Srs2 loading events at sites cleared of Rad51. We also demonstrate that Srs2 acts on heteroduplex DNA joints through two alternative pathways, both of which result in rapid disruption of the heteroduplex intermediate. On the basis of these findings, we present a model describing the recruitment and regulation of Srs2 as it acts upon homologous recombination intermediates. Kaniecki et al. develop a single-molecule assay for directly visualizing the behavior of the yeast helicase Srs2 as it acts upon single-stranded DNA (ssDNA) bound by the Rad51 recombinase. These experiments lead to a model describing the recruitment and regulation of Srs2 as it acts upon homologous recombination intermediates.